Orphan nuclear receptor NGFI-B forms dimers with nonclassical interface - Calgaro, Marcos R.; Neto, Mario de Oliveira; Figueira, Ana Carolina M.; Santos, Maria A.M.; Portugal, Rodrigo V.; Guzzi, Carolina A.; Saidemberg, Daniel M. [UNESP]; Bleicher, Lucas; Vernal, Javier; Fernandez, Pablo; Terenzi, Hernán; Palma, Mario Sergio [UNESP]; et al. (Wiley, 2007)
The orphan receptor nerve growth factor-induced B (NGFI-B) is a member of the nuclear receptor's subfamily 4A (Nr4a). NGFI-B was shown to be capable of binding both as a monomer to an extended half-site containing a single AAAGGTCA motif and also as a homodimer to a widely separated everted repeat, as opposed to a large number of nuclear receptors that recognize and bind specific DNA sequences predominantly as homo- and/or heterodimers. To unveil the structural organization of NGFI-B in solution, we determined the quaternary structure of the NGFI-B LBD by a combination of ab initio procedures from small-angle X-ray scattering (SAXS) data and hydrogen-deuterium exchange followed by mass spectrometry. Here we report that the protein forms dimers in solution with a radius of gyration of 2.9 nm and maximum dimension of 9.0 nm. We also show that the NGFI-B LBD dimer is V-shaped, with the opening angle significantly larger than that of classical dimer's exemplified by estrogen receptor (ER) or retinoid X receptor (RXR). Surprisingly, NGFI-B dimers formation does not occur via the classical nuclear receptor dimerization interface exemplified by ER and RXR, but instead, involves an extended surface area composed of the loop between helices 3 and 4 and C-terminal fraction of the helix 3. Remarkably, the NGFI-B dimer interface is similar to the dimerization interface earlier revealed for glucocorticoid nuclear receptor (GR), which might be relevant to the recognition of cognate DNA response elements by NGFI-B and to antagonism of NGFI-B-dependent transcription exercised by GR in cells. Published by Cold Spring Harbor Laboratory Press. Copyright © 2007 The Protein Society.
Keywords: Glucocorticoid nuclear receptor; Hydrogen-deuterium exchange; NGFI-B; Orphan nuclear receptor; SAXS; cell nucleus receptor; dimer; estrogen receptor; helix loop helix protein; nuclear receptor Nur77; retinoid X receptor; amino acid sequence; animal cell; controlled study; dimerization; fluorescence spectroscopy; mass spectrometry; nonhuman; priority journal; protein binding; protein conformation; protein folding; protein interaction; protein secondary structure; protein stability; protein structure; receptor binding; X ray crystallography; Circular Dichroism; Dimerization; DNA-Binding Proteins; Mass Spectrometry; Models, Biological; Models, Molecular; Protein Structure, Secondary; Receptors, Cytoplasmic and Nuclear; Receptors, Glucocorticoid; Receptors, Steroid; Scattering, Small Angle; Solutions; Transcription Factors